(untitled) (Revista de Artes Marciales Asiáticas, 2012)
This study explores the ways in which the construction and deconstruction of a martial arts-Daoism connection has figured in political ideology, national iden-tity, and commercial interest during the past 400 years of Chinese history. Focusing on the taijiquan-Daoism-Zhang Sanfeng nexus, it traces the wrapping of a martial art in indigenous religious garb during the periods of Manchu rule, Japanese occupation, and post-Mao 21st century. It concludes by reporting on a contemporary movement in China to revive the cult of Zhang Sanfeng and to cast taijiquan as a form of religious practice. In this light, taijiquan emerges as an important site of constructing “Chinese-ness” in the face of state appropriation and Western cultural imperialism.